Screening of Botanical Drugs against Lassa Virus Entry - Liu, Yang (J Virol, 2021)
Lassa virus (LASV) belongs to the Old World genus Mammarenavirus (family Arenaviridae). At present, there are no approved drugs or vaccines specific for LASV. In this study, high-throughput screening of a botanical drug library was performed against LASV entry using a pseudotype virus bearing the LASV envelope glycoprotein complex (GPC). Two compounds, bergamottin and casticin, were identified as micromolar-range inhibitors of LASV entry. A mechanistic study revealed that casticin inhibited LASV entry by blocking low-pH-induced membrane fusion. Analysis of adaptive mutants demonstrated that the F446L mutation, located in the transmembrane domain of GP2, conferred resistance to casticin. Furthermore, casticin antiviral activity extends to the New World pathogenic mammarenaviruses, and mutation of the conserved F446 also conferred resistance to casticin in these viruses. Unlike casticin, bergamottin showed little effect on LASV GPC-mediated membrane fusion, instead inhibiting LASV entry by blocking endocytic trafficking. Notably, both compounds showed inhibitory effects on authentic lymphocytic choriomeningitis virus. Our study shows that both casticin and bergamottin are candidates for LASV therapy and that the conserved F446 in LASV GPC is important in drug resistance in mammarenaviruses. IMPORTANCE Currently, there is no approved therapy to treat Lassa fever (LASF). Our goal was to identify potential candidate molecules for LASF therapy. Herein, we screened a botanical drug library and identified two compounds, casticin and bergamottin, that inhibited LASV entry via different mechanisms.